Pemberdayaan Pengrajin Dompet Kulit melalui Pelatihan Marketing Digital di Desa Babakan, Kecamatan Kopo, Kabupaten Serang - Haki, Ubay; Topo, Topo; Mercylia, Mercylia; Pahmina, Pahmina; Nurhaniyah, Nurhaniyah (Al-DYAS, 2025)
The primary challenge faced by leather wallet artisans in Babakan Jaya Village lies in limited marketing capabilities, which still rely on conventional methods such as word-of-mouth promotion and local networks. This community service program aims to enhance the artisans’ understanding and skills in digital marketing, particularly through the use of social media as a broader and more effective promotional tool. The methods implemented included classical training on the basics of digital marketing, hands-on product photography sessions, social media account creation, and on-site mentoring at production houses to identify challenges and provide contextual solutions. The results showed significant improvement across five key indicators: understanding of social media benefits increased by 55%, awareness of content consistency rose by 50%, mastery of product photography techniques improved by 50%, ability to craft persuasive product descriptions increased by 50%, and ownership of official Instagram/Facebook accounts rose by 60%. The study concludes that training and mentoring successfully enhanced artisans’ digital marketing capacity and opened up market expansion opportunities. The implications highlight the need for sustained mentoring programs, strengthened digital networking, and improved technological infrastructure to support the sustainable digital transformation of local MSMEs.